Ministry of Education (MOE) E9 Putrajaya / Tengku Putera Zunnurain Tengku Mustapah ... [et al.] - Tengku Putera Zunnurain, Tengku Mustapah; Siti Syazana Syafiqah, Osman; Siti Khadijah, Ahmad Taufix; Nurul Atikah, Dzulkefli (2019)
The purpose of this assignment is students are able to work in team or cooperation in carrying a task and how to use and implement the soft skills to persuade clients or persons to accept the group for findings. Besides, this course objective is to propose an integrated report consisting of multi-disciplinary approach for maintenance management with the selected building. The common problems faced during the site visit and interview is lack of information about the building either by person in charges which is building manager or by softcopy (documented). The building owner or manager should gain and collect more information about the building and the building details and must be documented for a future references. Apart from that, site visit are carry among three months which is four to five times and the data serene through an interview, fieldwork and documentation from the person in charge at the building. The data collected are recording either by writing, using camera and recording to create a findings of an assignment.